2008
DOI: 10.1007/s00213-008-1197-5
|View full text |Cite
|
Sign up to set email alerts
|

The reversal of amphetamine-induced locomotor activation by a selective neurotensin-1 receptor agonist does not exhibit tolerance

Abstract: Neurotensin-1 (NT1) receptor agonists have been proposed as putative antipsychotic drugs. Recently brain penetrating NT analogues produced by stability enhancing modification of the smallest NT fragment, , have demonstrated antipsychotic-like efficacy after acute systemic injection in several preclinical animal tests predictive for antipsychotic efficacy. However, the evidence regarding the persistence versus tolerance of these effects after repeated administration is ambiguous. Previous studies have used comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 24 publications
6
54
0
Order By: Relevance
“…Although lever-pressing behavior was still diminished the next day, it returned to normal levels by day 7. This confirmed conclusions by other investigators and us that activation of this NT system has a general inhibitory influence on METH-mediated behaviors that have a DA basis, and we now know that this probably includes some factors that are associated with drug self-administration (Wagstaff et al, 1994;Nicola 2007;Feifel et al, 2008). Pretreatment with the NT antagonist (SR48692) before days 5 to 7 enabled us to assess the state of endogenous NT release during METH selfadministration.…”
Section: Effect Of Methamphetamine Self-administration On Neurotensinsupporting
confidence: 87%
See 3 more Smart Citations
“…Although lever-pressing behavior was still diminished the next day, it returned to normal levels by day 7. This confirmed conclusions by other investigators and us that activation of this NT system has a general inhibitory influence on METH-mediated behaviors that have a DA basis, and we now know that this probably includes some factors that are associated with drug self-administration (Wagstaff et al, 1994;Nicola 2007;Feifel et al, 2008). Pretreatment with the NT antagonist (SR48692) before days 5 to 7 enabled us to assess the state of endogenous NT release during METH selfadministration.…”
Section: Effect Of Methamphetamine Self-administration On Neurotensinsupporting
confidence: 87%
“…Although little is known about its precise role, studies have suggested that NT has an inhibitory influence on the stimulatory behavioral effects of psychostimulants (Wagstaff et al, 1994;Chartoff et al, 2004;Feifel et al, 2008), possibly through an indirect mechanism involving increased striatal GABA activity and subsequent reduced DA release (Ferraro et al, 1998). This inhibitory action has been speculated to be of potential clinical value, suggesting that activation of NT receptors may have a neuroleptic action and be useful in the management of conditions of excessive DA activity (Chartoff et al, 2004;Feifel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D1 (SCH23390, R(1)-7-chloro-8-hydroxy-3-methyl-1-phenyl-2,3,4,5-tetrohydro-1H-3-benzazepine hydrochloride; Research Biochemicals Inc., Natick, MA) or D2 (eticlopride, S-(2)-3-chloro-5-ethyl-N-[(1-ethyl-2-pyrrolidinyl)methyl]-6-hydroxy-2-methoxybenzamide hydrochloride) antagonists were obtained commercially. A NTR1 agonist [PD149163 [a gift from the National Institute of Mental Health, NIH]; a stable NT fragment ) that stimulates CNS NTR1 receptors when delivered systemically; 0.25 or 0.5 mg/kg s.c.; Feifel et al, 2008] or antagonist [SR48692 [2-[(1-(7-chloro-4-quinolinyl)-5-(2,6-imethoxyphenyl)pyrazol-3-yl)carbonylamino]tricyclo(3.3.1.1. (3.7))decan-2-carboxylic acid; purchased from Tocris Bioscience]; 0.3 mg/kg; Wagstaff et al, 1994;Antonelli et al, 2007] was used to study the role of NT receptors in METH SA.…”
Section: Methodsmentioning
confidence: 99%